Mentoring improves the school-to-work transition of disadvantaged adolescents - Sven Resnjanskij; Jens Ruhose; Katharina Wedel; Simon Wiederhold; Ludger Woessmann (EconPol Forum, 2024)
Mentoring programs can strongly improve the transition from school to work for disadvantaged adolescents. Results from our field experiment indicate that a German mentoring program markedly boosts school achievement, patience, and labor-market orientation of students from highly disadvantaged backgrounds. The effects on math grades and labor-market orientation extend beyond the end of the program. Three years after program start, the mentoring program substantially increases the share of disadvantaged adolescents who start an apprenticeship, a vital step for success in the German labor market. The results show that substituting a lack of family support with other adults can help disadvantaged children in adolescen.
Keywords: 330